Aloha compadre : Latinxs in Hawaiʻi - Guevarra, Rudy P., Jr (Latinidad : transnational cultures in the United States, 2023)
"Aloha Compadre: Latinxs in Hawaiʻi is the first book to examine the collective history and contemporary experiences of the Latinx population of Hawaiʻi. This study reveals that contrary to popular discourse, Latinx migration to Hawaiʻi is not a recent event. In the national memory of the United States for example, the Latinx population of Hawaiʻi is often portrayed as recent arrivals and not as long-term historical communities with a presence that precedes the formation of statehood itself. Historically speaking Latinxs have been voyaging to the Hawaiian Islands for over 190 years. From the early 1830s to the present, they continue to help shape Hawaiʻi's history, yet their contributions are often overlooked. Latinxs have thus been a part of the cultural landscape of Hawaiʻi prior to annexation, territorial status, and statehood in 1959. Aloha Compadre also explores the expanding boundaries of Latinx migration beyond the western hemisphere and into Oceania"--